Implementasi Konsep Cheerful Learning Environment Melalui Penataan Ruang Kelas TK Qur’an Al-Ikhlas Desa Nagreg Kendan - Vivi Patra Komala; Rita Oktafil Marisa; Lisniawati Dwina; Ayu Nurul Hasna Kamilah; Putri Nuraeni (Jurnal Pengabdian Tri Bhakti, 2026)
The physical classroom environment plays a crucial role in supporting young children's engagement and learning comfort. However, many early childhood education institutions in rural areas still face limitations in creating stimulating and child-friendly classroom arrangements. This community service program aimed to implement the concept of a cheerful learning environment through classroom reorganization at TK Qur’an Al-Ikhlas. The program was conducted over one month using a participatory mentoring approach involving teachers in the stages of initial observation, classroom layout design, implementation of learning zones, and collaborative reflection. The classroom transformation included the establishment of four interactive learning zones (reading, art, role-play, and construction), flexible furniture arrangement, and optimization of locally sourced educational play materials. The results indicated significant improvements in both the visual and functional quality of the classroom, increased utilization of zone-based learning areas, and higher levels of children's active engagement during learning activities based on participatory observation. Furthermore, teachers demonstrated improved understanding of managing a child-centered learning environment. This program highlights that simple, collaborative interventions in classroom design can serve as an effective strategy to enhance the quality of early childhood learning environments sustainably.